Mental health in undergraduate students from Universidad Nacional Mayor de San Marcos School of Medicine - Perales, Alberto (2019)
Introduction. Previous studies pointed out mental health problems in undergraduate health students of School of Medicine from Universidad Nacional Mayor de San Marcos (UNMSM). Objective. To assess if there are differences between the frequency of mental health problems between first-year students and other years’ students from five professional schools of the UNMSM School of Medicine. Methods. A cross-sectional study. Validated instruments were used to assess mental health problems: suicidal intent, homicidal thinking, disocial behavior, alcoholism, depression and anguish. In addition, levels of resilience were evaluated. Students from all professional schools of the Faculty of Medicine were included in two analysis groups: first-year students and other years’ students. Results. 7,5% of suicide attempts, 18,9% of disocial behavior and 21,9% of homicidal thinking were found in first-year students. Similarly, 4,8% of alcoholism, 8,5% of depression and 3,2% of anxiety were found on same group of study. The frequency of mental health problems was higher according to the years of study, with statistically significant differences only in depression, anxiety and alcoholism. 29,3% of respondents have a low level of resilience Conclusion. Concerning frequencies of mental health problems were found in undergraduate students of UNMSM School of Medicine, although a percentage of students were admitted in university with mental health problems. The university environment would be an aggravating factor in depression, anxiety and alcohol problems.